2021
DOI: 10.1080/22423982.2021.1946324
|View full text |Cite
|
Sign up to set email alerts
|

Acute health care among Indigenous patients in Canada: a scoping review

Abstract: A recent report by the Chief Public Health Officer of Canada demonstrates the inferior health status of Indigenous Peoples in Canada when compared to non-Indigenous populations. This scoping review maps out the available literature concerning acute health care for Indigenous Peoples in Canada in order to better understand the health care issues they face. All existing articles concerning health care provided to Indigenous Peoples in Canada in acute settings were included in this review. The targeted studied ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“… 20 Furthermore, Indigenous peoples present more commonly for acute health care but report lower levels of satisfaction with and access to health care, illustrating the need for both a better understanding of gaps across the care continuum and the development of a culturally safe environment. 33 We found that contemporary issues pertaining to systemic barriers and the social determinants of health of Indigenous peoples in Canada are generally well described, although a minority of articles discussed the historical context and drivers of current disparities and inequities. Additionally, none of the identified studies applied indigenous methods or methodologies in conducting their research, limiting the integration of traditional medicine and a qualitative understanding of Indigenous peoples’ barriers to and lived experiences with cardiovascular care in Canada, based on the current review.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“… 20 Furthermore, Indigenous peoples present more commonly for acute health care but report lower levels of satisfaction with and access to health care, illustrating the need for both a better understanding of gaps across the care continuum and the development of a culturally safe environment. 33 We found that contemporary issues pertaining to systemic barriers and the social determinants of health of Indigenous peoples in Canada are generally well described, although a minority of articles discussed the historical context and drivers of current disparities and inequities. Additionally, none of the identified studies applied indigenous methods or methodologies in conducting their research, limiting the integration of traditional medicine and a qualitative understanding of Indigenous peoples’ barriers to and lived experiences with cardiovascular care in Canada, based on the current review.…”
Section: Discussionmentioning
confidence: 90%
“…As a result, Indigenous peoples in Canada are faced with substantially longer times between the onset of symptoms and hospital presentation compared to those in the general population. 33 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across various ethnically diverse non-Indigenous populations, hospitalisation and mortality data have been well documented in the literature ( 3 9 , 21 23 , 28 31 ). Although the available reports suggest that the burden of chronic respiratory disorders is much higher among global First Nations Indigenous people (including higher heath care utilisation and hospital admission rates), there is scant evidence pertaining to factors that may predict mortality or survival among First Nations Indigenous people ( 20 , 32 38 ).…”
Section: Discussionmentioning
confidence: 99%